Penerapan Model Pembelajaran Attentuion, Relevance, Confidence, And Satisfaction (ARCS) untuk Meningkatkan Hasil Belajar IPA - Aini, Zumratul; Ali, Lalu Usman; Ernita, Nevi (CAHAYA: Journal of Research on Science Education, 2025)
The purpose of this research is to find out the application of the ARCS learning model can improve science learning outcomes for students of class VIII A at MTs Darul Ihsan Lelong, to find out student responses to the application of the Attention, Relevance, Confidence, and Satisfaction (ARCS) learning model for class VIII A at MTs Darul Ihsan Auction,. The research subjects were class VIII A students of MTs Darul Ihsan Lelong. This type of research is Classroom Research. In this study there are two variables, the dependent variable is the results of students' science learning and the independent variable is the application of the ARCS learning model in science learning. Based on the results of the analysis of student learning evaluation, it was obtained that classical mastery (KK) in cycle II was 90%, we can see that the percentage of classical completeness has met the classical completeness target of 85%. From the results of this study it can be concluded that the application of the ARCS learning model can improve student learning outcomes, especially in science subjects about substance stress. The results of the student response questionnaire have reached the category that is strongly agree (SS) with a percentage of 87.08%.